Handbook of Stress in the Occupations
DOI: 10.4337/9780857931153.00050
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Farm Entrepreneurs

Abstract: Current features and characteristics of agricultureAgriculture is an old and traditional occupational sector that utilizes natural resources. The rural environment is sometimes characterized as a peaceful living environment. Today, the operational environment of farm entrepreneurs also includes economic and political decisions. The circumstances of farm enterprises can perhaps be explained by the historical background of society. On a farm, technological equipment and development, buildings and social relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…38 A literature review that gathered research results from 15 scientific articles identified the following as the most common stressors among farm entrepreneurs: (a) the farm economy; (b) regulations, including farming bureaucracy, the amount of paperwork, and the political framework related to agriculture; (c) the weather and natural conditions of agriculture; and (d) dangers in farm work, injuries, and deficiencies in the work environment. 39 A study in England and Wales investigated sources of stress for farmers in general and found that they had problems with record keeping and paperwork (62%), difficulty understanding forms (56%), and problems arising from the effects of new legislation and regulations (49%). 40 Nearly a quarter reported financial problems and most were worried about money.…”
Section: Mental Health Problems and Stress Associated With Psychosocimentioning
confidence: 99%
“…38 A literature review that gathered research results from 15 scientific articles identified the following as the most common stressors among farm entrepreneurs: (a) the farm economy; (b) regulations, including farming bureaucracy, the amount of paperwork, and the political framework related to agriculture; (c) the weather and natural conditions of agriculture; and (d) dangers in farm work, injuries, and deficiencies in the work environment. 39 A study in England and Wales investigated sources of stress for farmers in general and found that they had problems with record keeping and paperwork (62%), difficulty understanding forms (56%), and problems arising from the effects of new legislation and regulations (49%). 40 Nearly a quarter reported financial problems and most were worried about money.…”
Section: Mental Health Problems and Stress Associated With Psychosocimentioning
confidence: 99%
“…High work centrality may be associated with commitment to work and job satisfaction; very high work centrality is related to insufficient and few social relations 20) . A study of stress among Finnish farmers, working in a sector populated with small-scale enterprises, concluded good social relationships with friends and family are important for avoiding stress at work 21) . In a cross-sectional study of entrepreneurs living in the central region of Sweden 22) , poor job satisfaction was the strongest work-related factor for poor self-reported health among working conditions, such as poor physical work environment, monotonous work, poor influence over work, and long work hours.…”
mentioning
confidence: 99%
“…Over the past 30 years, a number of research studies have examined the role that stressors play in the lives of farmers and the relationship between stressors and various health outcomes, including mental health problems [11][12][13][14], suicide [15][16][17][18], injuries [19][20], working conditions [21], job satisfaction [22], and general well-being [2,[21][22][23][24][25][26][27]. Human stress reactions have a common physiological basis, but individuals manifest stress differently depending on their situation [8].…”
mentioning
confidence: 99%